Karakteristik Soal UASBN Mata Pelajaran Sejarah di SMA N 7 Padang dan SMA Pembangunan Laboratorium UNP - Nilawati Nilawati; Ofianto Ofianto (Jurnal Halaqah, 2019)
This study aims to get a clear picture of the characteristics of the National Standard School Final Examination subjects in the history of specialization in class XII in SMA N 7 Padang and SMA UNP Laboratory Development in the 2018/2019 school year in terms of the quality of the tests which include: validity, reliability, errors measurement (standard error of measurement / SEM), and in terms of the quality of items that include: Distinguishing Power, Difficulty Level and Effectiveness of Deception. The research approach used is quantitative research, where the data obtained in the form of numbers are then analyzed with the Item and Test Analysis (ITEMAN) program, then described descriptively. This type of research is quantitative descriptive research. The results of this study indicate that the quality of the analysis of items in SMA N 7 Padang is better, this is indicated in: (1) The validity of items is 26 items (65%) while in SMA Pembangunan the validity of valid items is 23 items (57.5% ), (2) Test reliability is 0.592 while in SMA Pembangunan is 0.448, (3) Measurement error / SEM is 2,960 while in SMA Pembangunan is 3,027 meaning the smaller the SEM number, the better the quality of the questions, (4) The different power of the questions as many as 18 items enough category (45%) while in SMA Pembangunan as many as 14 items (35%), (5) Effectiveness of deception as many as 18 items (45%) while in SMA Pembangunan as many as 16 items (40%).